Principles of neuromusculoskeletal coordination in human cycling - Robinson, A. (Manchester Metropolitan University, 2020)
Optimisation of movement strategies during cycling is an area which has gathered a lot of attention over the past decade. Resolutions to augment performance have involved manipulations of bicycle mechanics, including chainring geometries. Elliptical chainrings are proposed to provide a greater effective diameter during the downstroke, manipulating mechanical leverage and resulting in greater power production during this period. A review of the literature indicates that there is a pervasive gap in our understanding of how the theoretical underpinnings of elliptical chainrings might be translated to practical use. Despite reasonable theory of how these chainrings might enforce a variation in crank angular velocity and consequently alter force production, performance-based analyses have struggled to present evidence of this. The purpose of this thesis was to provide a novel approach to this problem by combining experimental data with musculoskeletal modelling and evaluating how elliptical chainrings might influence crank reactive forces, joint kinematics, muscle-tendon unit behaviour and muscle activation. One main study was proposed to execute this analysis, and an anatomically constrained model was subsequently used to determine the joint kinematics and muscle-tendon unit behaviour. Bespoke elliptical chainrings were designed for this study and as such, different levels of chainring eccentricity (i.e. ratio of major to minor axis) and positioning against the crank were presented whilst controlling the influence of other variables known to affect the neuromuscular system such as cadence and load. Findings presented in this thesis makes a new and major contribution in our understanding of the neuromusculoskeletal adaptations which occur when using elliptical chainrings, showing alterations in crank reaction force, muscle-tendon unit velocities, joint kinematics and muscle excitation over a range of cadences and loads, and provides direction for where the future of this research might be best applied.